UPAYA MOLDOVA MENGATASI KRISIS ENERGI AKIBAT PERANG RUSIA UKRAINA TAHUN 2022 - Azmi, Agus Nilmada; Suwignyo, Tresnaningsih (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The Russia-Ukraine war that began in February 2022 has had a lot of impact on surrounding countries. One of the impacts that has received a lot of attention is the energy crisis. Moldova is one of the countries affected by the energy crisis because of its dependence on supplies from Russia. The effects of the energy crisis are widespread in people's lives. Due to the energy crisis, there is economic, social, and political instability in the country. This study seeks to explore the various efforts made by Moldova to overcome the energy crisis. This study used data from secondary sources collected through literature studies. The data found is then analyzed with qualitative analysis techniques. The results of this study show that Moldova is diversifying its energy supply sources by exploring cooperation with other energy-producing countries. Moldova is also conducting energy diplomacy in an effort to obtain financial and technical support to overcome the ongoing energy crisis.